An Integrated Production Inventory Model for Repairable Items with Uncertain Lead time - Dr Sanjay Kumar Sharma; Er Himanshu Tripathi (Genius Journals, 2021)
The integrated Much focus has been placed on inventory policy recently as a means of preserving a competitive edge. The integrated inventory model has been the subject of numerous studies
Keywords: Integrated inventory, competitive edge